Short-period linear array reveals velocity structure and fault development characteristics of the shallow crust in the Xuancheng area - Jie Fang; Huajian Yao; Jie Li; Junlun Li; Guili Zhou (地球与行星物理论评)
Xuancheng City is situated in the transitional zone between the southeastern hills and the middle and lower reaches of the Yangtze River plain. This region has undergone multiple stages of tectonic activity, resulting in complex geological structures and well-developed fault systems. Investigating the shallow velocity structure and fault zones in the Xuancheng area not only enhances our understanding of the region's geological structure and mineralization but also provides an important reference model for assessing regional seismic risks and hazards. A short-period linear array consisting of 110 three-component seismometers was deployed in the study area. Using one month of collected three-component ambient noise data, the horizontal-to-vertical spectral ratio (HVSR) method was applied to detect site peak frequency and the bedrock interface structure. The empirical Green's functions were reconstructed from the vertical ambient noise data, and the phase velocity dispersion curve was extracted using the extended range phase shift (ERPS) method. Based on the site peak frequency and bedrock interface burial depth derived from HVSR, the structure of the shallow, loose sedimentary layers along the survey line was delineated. The results indicate that bedrock depth in the southern Anhui mountainous region is relatively shallow, whereas it is deeper in the basin areas. The thickness of the loose surface sedimentary layer can reach up to 80 m below ground. Furthermore, a seismic damage assessment and earthquake resistance evaluation of buildings in the area revealed that the average amplification factor of ground motion is relatively high. Localized areas may experience significant seismic amplification effects, warranting special attention to the earthquake resistance of low-rise buildings (1-2 stories) in the southern Anhui mountainous region and high-rise buildings (7 stories or more) in the Xuancheng-Nanling basin. According to the inverted 2D shear wave velocity model, the structure of the shallow crust down to a depth of 6 km in the study area was obtained. The findings reveal that the Xuancheng-Nanling basin exhibits significant low-velocity characteristics in the shallow layers, with the basement depth extending to approximately 2 km. Additionally, certain parts of the basin display high-velocity anomalies, suggesting the presence of magmatic intrusions and thrust nappe tectonic activity resulting from multiple tectonic events. The deep crust in the area generally shows a "shingle-like" pattern of alternating high- and low-velocity anomalies. These multiple low-velocity anomaly zones are inferred to correspond to the structural damage zones of the Zhouwang, Jiangnan, Maoshan, and Qingshuihe-Hewan faults, highlighting the intense deformation caused by repeated phases of compressional and extensional tectonic reworking in the region. Based on these findings, this study provides a new basis for analyzing geological structure conditions, evaluating seismic risks and hazards, and advancing regional prospecting and exploration efforts in the Xuancheng area.